Initial Stages in the Formation of Cu2ZnSn(S, Se)4 Nanoparticles. Issue 47 (21st October 2013) - Hou, Bo; Benito‐Alifonso, David; Kattan, Nessrin; Cherns, David; Galan, M. Carmen; Fermín, David J.
<x xml:space="preserve">Abstract</x> In the beginning: Intermediate species generated in the synthesis of Cu2ZnSn(S, Se)4 nanoparticles (see figure) in oleylamine have been identified. The solvent plays a central role in the reaction mechanism, determining the composition of the nanostructures.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>